2018
DOI: 10.3390/chemengineering2020024
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Polymers Grafted onto Multifunctional Mesoporous Silica Nanoparticles for Gene Delivery

Abstract: Biodegradable polymer possesses significant potential for applications in different fields, since flexibility gives rise to materials with great physical and mechanical property diversity. The poly-caprolactone (PCL) and chitosan derivatives (CS) have the ability to form scaffolds, which adhere to the surface of mesoporous silica nanoparticles (MSNs) and its porous networks. The novel characteristics of the developed PCL/MSNs and CS/MSNs, such as very low in vivo degradation rate, ordered pore network, uniform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…29,86,93,94 These results also indicate that 1,3,5-tris(2-hydroxyethyl)isocyanurate has been successfully grafted onto the surface of MCM-41. 95…”
Section: Resultsmentioning
confidence: 99%
“…29,86,93,94 These results also indicate that 1,3,5-tris(2-hydroxyethyl)isocyanurate has been successfully grafted onto the surface of MCM-41. 95…”
Section: Resultsmentioning
confidence: 99%
“…After performing motor co-ordination tests to determine the biochemistry of blood, animals were anesthetized with thiopental (80 mg/kg, i.p). Then, blood was collected from the abdominal aorta, moved to standard tubes (Heparin-coated tubes), and centrifuged (3000 g, for 15…”
Section: Gait Testmentioning
confidence: 99%
“… 9 In past years, various investigations have been carried out on the adsorption of heavy metals by mesoporous silica. 10 , 11 These studies resulted in the development of a novel application for MS materials in sensors, 12 catalysts, 13 drug delivery carrier, 14 gene delivery, 15 an adsorbent 16 , 17 and also as an antidote agent. 13 In this regard, Farjadian et al reported that EDTA modified MS could be potent antidote agents while assessed in vitro and in vivo in adsorption of iron 18 and copper.…”
Section: Introductionmentioning
confidence: 99%
“…Polycaprolactone (PCL) was bound on to the NH 2 -MNP particles via thermal coupling, based on a method published previously. 18 In brief, 100 mg of NH 2 -MNP (from section 2.2.2) were suspended in 20 mL of dry toluene in a round bottom flask (250 mL) and sonicated at 70°C until full dispersion. PCL (2 g) was dissolved separately in 20 mL of dry toluene and heated to 70°C.…”
Section: Polycaprolactone (Pcl) Coating Onto Nh 2 -Mnpmentioning
confidence: 99%